Escherichia coli Type III Secretion System 2 ATPase EivC Is Involved in the Motility and Virulence of Avian Pathogenic Escherichia coli - Wang, Shaohui; Liu, Xin; Xu, Xuan; Yang, Denghui; Wang, Dong; Han, Xiangan; Shi, Yonghong; Tian, Mingxing; Ding, Chan; Peng, Daxin; Yu, Shengqing (Frontiers in Microbiology, 2016)
Type III secretion systems (T3SSs) are crucial for bacterial infections because they deliver effector proteins into host cells. The Escherichia coli type III secretion system 2 (ETT2) is present in the majority of E. coli strains, and although it is degenerate, ETT2 regulates bacterial virulence. An ATPase is essential for T3SS secretion, but the function of the ETT2 ATPase has not been demonstrated. Here we show that EivC is homologous to the β subunit of F0F1 ATPases and it possesses ATPase activity. To investigate the effects of ETT2 ATPase EivC on the phenotype and virulence of avian pathogenic Escherichia coli (APEC), eivC mutant and complemented strains were constructed and characterized. Inactivation of eivC led to impaired flagella production and augmented fimbriae on the bacterial surface, and, consequently, reduced bacterial motility. In addition, the eivC mutant strain exhibited attenuated virulence in ducks, diminished serum resistance, reduced survival in macrophage cells and in ducks, upregulated fimbrial gene expression, and downregulated flagellar and virulence gene expression. The expression of the inflammatory cytokines interleukin (IL)-1β and IL-8 were increased in HD-11 macrophages infected with the eivC mutant strain, compared with the wild-type strain. These virulence-related phenotypes were restored by genetic complementation. These findings demonstrate that ETT2 ATPase EivC is involved in the motility and pathogenicity of APEC.